1993
DOI: 10.1159/000182740
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Catecholamine Metabolism during Bromocriptine Treatment in Polycystic Ovary Syndrome

Abstract: The role of dopaminomimetic drugs on the brain catecholamine metabolism in the neuroendocrine regulation of the polycystic ovary syndrome (PCO) was investigated. We measured, besides peptide hormones and sex steroids, urinary dopamine (DA), norepinephrine, epinephrine, vanillylmandelic acid, homovanillic acid (HVA), 3,4-dihydroxyphenylacetic acid (DOPAC) and total 3-methoxy-4-hydroxyphenylglycol (MHPG) levels by high-performance liquid chromatography with electrochemical detector in 10 women with PCO before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…A number of studies in adult PCO patients (Paradisi et al, 1989;Yoshino et al, 1992;Shoupe & Lobo, 1984) have also shown urinary levels of catecholamines and VMA within the control range but to our knowledge plasma levels of catecholamines or Dopa have not been reported previously in PCO. A number of studies in adult PCO patients (Paradisi et al, 1989;Yoshino et al, 1992;Shoupe & Lobo, 1984) have also shown urinary levels of catecholamines and VMA within the control range but to our knowledge plasma levels of catecholamines or Dopa have not been reported previously in PCO.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…A number of studies in adult PCO patients (Paradisi et al, 1989;Yoshino et al, 1992;Shoupe & Lobo, 1984) have also shown urinary levels of catecholamines and VMA within the control range but to our knowledge plasma levels of catecholamines or Dopa have not been reported previously in PCO. A number of studies in adult PCO patients (Paradisi et al, 1989;Yoshino et al, 1992;Shoupe & Lobo, 1984) have also shown urinary levels of catecholamines and VMA within the control range but to our knowledge plasma levels of catecholamines or Dopa have not been reported previously in PCO.…”
Section: Discussionmentioning
confidence: 69%
“…These findings were interpreted as supporting the suggestion of both decreased dopaminergic control of LH secretion and increased noradrenergic activity in hypothalamic GnRH neurons in PCO syndrome. (Paradisi et al, 1993;Yoshino et al, 1992;Shoupe & Lobo, 1984). Nevertheless, further research in the field has cast some doubts on these interpretations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] Beneficial effects of bromocriptine on glucose and lipid metabolism are mediated by an increase in dopaminergic tone within the central nervous system, 25 and this drug was also found to stimulate central dopaminergic transmission in women with polycystic ovary syndrome. 26 Interestingly, abnormalities in pituitary hormone secretion in polycystic ovary syndrome seem to be a consequence of relative central dopaminergic failure. 27 A similar failure may also occur in men with early-onset androgenic alopecia because their hormonal profile resembles that of women with polycystic ovary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results may be also associated with a different effect of bromocriptine on insulin sensitivity, which was stronger in men with normal hair growth than in men with early‐onset androgenic alopecia, as well as correlating positively with the extent of changes in uric acid, hsCRP, fibrinogen, homocysteine, and UACR. Moreover, they may result from the impact on dopaminergic transmission 25–27 . Beneficial effects of bromocriptine on glucose and lipid metabolism are mediated by an increase in dopaminergic tone within the central nervous system, 25 and this drug was also found to stimulate central dopaminergic transmission in women with polycystic ovary syndrome 26 .…”
Section: Discussionmentioning
confidence: 99%